2020
DOI: 10.1029/2020jd033275
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Urban Hydrological Processes in Mitigating Urban Heat Island and Human Thermal Stress During a Heat Wave Event in Nanjing, China

Abstract: Over the past 40 years, the urbanization process has developed rapidly all over the world. This is especially so in China, where the urbanization rate has reached 59.58% in 2018, and more than 831.37 million people live in cities (X. Li et al., 2019). Rapid urbanization has introduced many adverse effects, such as urban heat islands (UHIs; Y. Chen & Zhang, 2018), heavier rainfall (Miao et al., 2011), storm floods (Ntelekos et al., 2010), and air pollution (Baklanov et al., 2016). The UHI effect, in which urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 67 publications
(199 reference statements)
3
5
0
Order By: Relevance
“…consistently decreases over all the urban land categories after the urbanization, especially the decreases are relatively larger in the nighttime with the maximum exceeding 0.5. This is in agreement with existing simulations and observations that the surfacelayer atmosphere is more unstable in the urban areas than in the surrounding countryside areas (Chen and Zhang 2018, Huszar et al 2018, Wang et al 2020, especially in the nighttime when there often exists a nearneutral to stable boundary-layer in the surrounding countryside areas (Barlow et al 2011). More unstable atmosphere is favorable to inducing and maintaining stronger turbulent motion and convection (Barlow 2014), which thus enhances the wind gust in the urban areas.…”
Section: Diurnal Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…consistently decreases over all the urban land categories after the urbanization, especially the decreases are relatively larger in the nighttime with the maximum exceeding 0.5. This is in agreement with existing simulations and observations that the surfacelayer atmosphere is more unstable in the urban areas than in the surrounding countryside areas (Chen and Zhang 2018, Huszar et al 2018, Wang et al 2020, especially in the nighttime when there often exists a nearneutral to stable boundary-layer in the surrounding countryside areas (Barlow et al 2011). More unstable atmosphere is favorable to inducing and maintaining stronger turbulent motion and convection (Barlow 2014), which thus enhances the wind gust in the urban areas.…”
Section: Diurnal Variationsupporting
confidence: 92%
“…The daytime mean wind speed in LIR urban areas reduces by approximately 0.1-0.2 m s −1 (8%-12%), and the reduction of the mean wind speed increases with the increase of building density, as the largest reduction is in COI urban areas where it reduces by approximately 0.5 m s −1 (20%), implying that stronger drag force and greater roughness length make larger wind speed reduction, which is in agreement with prior studies (Liao et al 2015, Wang et al 2019. The nighttime wind speed reduction is less than that at daytime, being between 0.1-0.3 m s −1 (4%-8%) over most urban areas, which could be because the PBL is more stable and the wind speed is generally smaller in the nighttime, thus leading to less change of the nighttime wind speed (Wang et al 2020). The daily mean wind speed reduces between 0.2-0.4 m s −1 (8%-16%) in most urban areas, which is consistent with prior studies simulating the effects of urbanization on wind speed (Wang et al 2014, Yang et al 2015, Huszar et al 2018.…”
Section: Spatial Variationsupporting
confidence: 91%
“…For instance, Masson, Lion, Peter, Pigeon, Buyck and Brun [94] studied the effects of landscape change (forest, local farming and water) coupled with reflective surface coverage and found that the UHI in Paris can be reduced by 2-3 K. Zhou and Shepherd [105] revealed that the cooling effect of combined albedo change and green space is not as significant as individual strategies during HW days. The combination of five different urban hydrological processes, including anthropogenic latent heat, urban oasis effect, urban irrigation, evaporation from paved surfaces and green roofs, was studied by Wang, Liu, Miao, Wu, Zhang and Qiao [97]. They found that the urban hydrological processes can effectively mitigate UHI surf and UHI UBL , and the effectiveness is more distinct with reduced density of urbanization.…”
Section: Combined Strategiesmentioning
confidence: 99%
“…Relative humidity (RH) and wind speed (WS) are also critical in heatwave processes, and RH and WS can substantially modulate impacts of heatwaves on thermoregulation 15,16 . Unfortunately, few studies have introduced these two variables into the analysis of heatwaves 9,16,17 .So far, few efforts have been directed to moist heat stress risk (MHSR) considering MHS (moist heat stress), population, GDP, and vegetation cover across China, though MHS has disastrous effects on human health as well as socioeconomy 18,19 , and particularly the exposure and vulnerability under MHS [20][21][22] . A bunch of studies analyzed differences amongst people given impacts by high temperature from viewpoints of population density, gender, age, education, income, housing quality, pre-existing medical conditions, minority status, poverty, social networks, home amenities (e.g., air conditioning) 19,21,23,24 , implying significance of exposure to MHS.…”
mentioning
confidence: 99%
“…Relative humidity (RH) and wind speed (WS) are also critical in heatwave processes, and RH and WS can substantially modulate impacts of heatwaves on thermoregulation 15,16 . Unfortunately, few studies have introduced these two variables into the analysis of heatwaves 9,16,17 .…”
mentioning
confidence: 99%